Hubungan Stres Akademik Dan Kualitas Tidur Terhadap Sindrom Pramenstruasi Selama Pembelajaran Daring Di Masa Pandemi COVID-19 - Arlia Fika Damayanti; Dora Samaria (Jurnal Keperawatan, 2021)
Premenstrual syndrome is the most common disorder experienced by women of childbearing age. There are various factors that can worsen the degree of premenstrual syndrome, including stress levels, sleep quality, nutritional status, smoking and alcohol. Various limitations during the distance learning process in the period of Covid-19 pandemic increased the academic stress and bad sleep quality of the students. This study aims to determine the relationship of academic stress and sleep quality to the degree of premenstrual syndrome in the Undergraduate Nursing students of Universitas Pembangunan Nasional Veteran Jakarta during the distance learning process in the period of the Covid-19 pandemic. This study used Cross sectional research design with a sample number of 160 respondents through Stratified Random Sampling method. Data collection is done through google form’s questionnaire using Student-Life Stress Inventory (SLSI), Pittsburgh Sleep Quality Index (PSQI) and The Shortened Premenstrual Assessment Form (SPAF) that have undergone the validity and reliability test. The result showed that there was a significant relationship between academic stress (p-value 0.000) and sleep quality (p-value 0.000) to the degree of premenstrual syndrome. This study recommends that students be able to manage and control academic stress conditions and sleep quality well to reduce the risk of premenstrual syndrome.